UPAYA MENINGKATKAN KEMAMPUAN MENGURUTAN (SERIASI) UKURAN MELALUI PERMAIANAN MOBIL PINTAR ANAK USIA 4-5 DI TAMAN KANAK-KANAK LABSCHOOL FIP UMJ - Andriyani (CV. Multi Kreasi Media, 2024)
The ability to determine the order (seriation) of size is the accuracy possessed by children in determining a size order from various existing sizes. Seriation competence in children aged 4-5 years is to order objects from the largest to the smallest or vice versa as many as 5 seriations. In reality, 10 out of 15 children still have deficiencies in ordering sizes. This study aims to improve children's learning outcomes in determining the order of size and to improve the quality of learning so that activities can run effectively, efficiently, and enjoyably. The results of the study showed that there was an increase in the ability to order (seriation) of size based on the results of children's learning achievements during pre-action to cycle II by 86%. The application of smart car games can improve the quality of learning to be more interesting and efficient.